Neurological Manifestations among Dengue Patients in an Endemic Population: Insights from a Tertiary Care Hospital in Bangladesh (Journal of the Medical College for Women & Hospital, 2026)
Background: Dengue virus infection is a major public health concern in tropical and subtropical regions, and neurological complications are increasingly recognized as part of its clinical spectrum. Despite their clinical significance, data on neurological dengue from endemic settings such as Bangladesh remain limited. Aim: To describe the spectrum, laboratory correlates, and outcomes of neurological manifestations among dengue patients admitted to a tertiary Medical College Hospital in Bangladesh. Materials and Method: This cross-sectional  study was conducted at the department of Neurology, Dhaka Medical College Hospital, from June 2024 to July 2025. A total of 48 laboratory-confirmed dengue patients with neurological manifestations were consecutively enrolled. Clinical, laboratory, cerebrospinal fluid (CSF), and neuroimaging findings were recorded. Outcomes were assessed at discharge. Results: The mean age of patients was 34.2 ± 14.8 years, with a male predominance (58%). The most frequent neurological manifestation was encephalitis (47.9%), followed by meningitis (29.2%), seizures (18.8%), and Guillain–Barré syndrome (4.1%). Thrombocytopenia (91.7%), leukopenia (83.3%), and elevated liver enzymes (72.9%) were common laboratory abnormalities. CSF pleocytosis was significantly associated with encephalitis and meningitis (p=0.02), and thrombocytopenia correlated with encephalitis and seizures (p=0.04). Neuroimaging abnormalities were observed in 46.2% of those imaged. At discharge, 79.2% recovered without sequelae, 12.5% had mild to moderate deficits, 4.2% had severe disability, and mortality was 4.2%, deaths were due to encephalitis. Conclusion: Neurological manifestations in dengue, though uncommon, contribute substantially to morbidity and mortality, with encephalitis being the most severe and fatal presentation. Early recognition, prompt management, and structured follow-up are critical to improve outcomes and reduce long-term disability in endemic regions.J Med Coll Women Hosp.2026; 22(1): 156-164